Glory of fire retardants in Li-ion batteries: could they be intrinsically safer? - Mishra, Rajat; Anne, Mounika; Das, Sayan; Chavva, Tarunikaa; Shelke, Manjusha V.; Pol, Vilas G. (Advanced Sustainable Systems, 2024)
Lithium-ion batteries (LIBs) have dramatically transformed modern energy storage, powering a wide range of devices from portable electronics to electric vehicles, yet the use of flammable liquid electrolytes raises thermal safety concerns. Researchers have investigated several ways to enhance LIB's fire resistance. Fire retarding molecules functions through cooling effects, scavenging radicals, and forming protective barriers. Incorporating fire-suppressing molecules within the LIBs aims to delay or mitigate thermal runaway scenarios, reducing the risks of fires or explosions. Achieving an optimal balance between safety and performance is a major obstacle in the design of intrinsically safer LIBs. Therefore, it is important to consider their effects on LIB's performance, long-term stability, and environmental impact. To overcome these challenges, collaborative research efforts among academia, industry, and regulatory sectors are necessary. This article reviews state-of-the-art literature associated with LIBs safety or even fire mitigation by introducing solid-state or quasi-solid-state electrolytes as well as modified liquid electrolytes. Moreover, the effectiveness of various strategies in making LIBs intrinsically safer is critically evaluated with an emphasis on fire retardants followed by shedding some light on the remaining challenges.

Wide temperature enhanced sodium storage in tailored, sustainable sodiophilic biphasic N-doped carbon - Yadav, Poonam; Das, Anoushka K.; Torris, Arun; Wasnik, Kundan; Koppisetti, Heramba Venkata Sai Rama Murthy; Pol, Vilas G.; Shelke, Vilas; Shelke, Manjusha (Materials Today Chemistry, 2024)
Alternative to Li-ion batteries(LIB), Na-ion batteries (NIB) and Na metal batteries (NMB) are gaining significant attention due to their low cost, abundance, and safety. By modulating microstructural properties such as graphitization, heteroatom doping, surface-rich functional groups, and interlayer d-spacing, Na-ion storage in NIB and Na plating/striping in NMB can be ameliorated. This study reports sodiophilic N-doped polymer-derived carbon (PDC) as an anode for NIB and host for Na metal in NMB. As NIB anode, PDC provides a storage capacity of 173 mAh g- 1 at 1 A g- 1 in half-cell and 84 mAh g- 1 at 1C (1C = 128 mAhg- 1) in full-cell with Na3V2(PO4)2F3 (NVPF) cathode. As Na metal anode (NMA) host, a high columbic efficiency (C.E.) of 99.45% for over 1000 cycles at 6 mA cm- 2_4 mAh cm-2 is obtained. Furthermore, fascinating wide temperature (50 degrees C and -20 degrees C) sodiumion storage is successfully demonstrated by PDC. Advanced X-ray photoelectron spectroscopy (XPS) confirmed the formation of stable and uniform solid electrolyte interphase (SEI) composed of inorganic and organic components, X-ray microtomography confirmed uniform Na plating throughout the volume of the electrode analogous to Brunauer-Emmett-Teller (BET) surface area, Raman spectroscopy, X-ray diffraction (XRD) and high-resolution transmission electron microscopy (HRTEM) results. A sustainable and scalable promising biphasic NIB anode and sodiophilic host for Na metal was possible due to larger d-spacing, partial graphitization, high mesoporosity, N-doping, presence of surface functional groups, better charge transfer, and diffusion properties.
Keywords: Full-cell; Low and elevated temperatures; Na metal host; Polymer-derived carbon; Sodium-ion battery; X-ray tomography

Evaluating sodium-ion pouch cell battery for renewable energy storage under extreme conditions - Shelke, Mehul; Boyer, Jamee M.; Mirzapure, Vinay; Pol, Vilas G. (Communications Chemistry, 2025)
A sodium-ion battery (SIB) is a sustainable energy storage technology based on abundantly available raw materials. It is a commercially viable option because of the processing similarity with Li-ion battery. Most of the energy storage studies focus on the near room temperature performance of different battery chemistries. Herein, we report the ultralow temperature performance of the SIB pouch cell. The cells fabricated using low-temperature compatible components showed significant specific energy values around 96, 74, and 46 Wh kg-1 at room temperature, -25 degrees C, and -50 degrees C, respectively. We demonstrated the battery performance under laboratory conditions as well as under actual windy and snowy environments. Such an exhibition highlights the use case of the SIB pouch cell as an emergency energy storage device in extreme weather conditions. Moreover, charging of SIB cell at -100 degrees C using polycrystalline Si solar cell is also reported, indicating the possibility of deployment for space expeditions.

Insights into electrolyte-solvent interactions and SEI formation for sustainable sodium-ion battery operation at low temperatures - Kim, Soohwan; Mirzapure, Vinay; Atwi, Rasha; Koppisetti, Heramba V. S. R. M.; Wasnik, Kundan; Rajput, Nav Nidhi; Shelke, Manjusha; Pol, Vilas G. (Small Methods, 2025)
Sodium-ion batteries (SIBs) show promise as an alternative to lithium-ion batteries. However, they face performance challenges at ultra-low temperatures (<-40 degrees C) due to slow Na+ transfer kinetics with conventional electrolytes. This limitation restricts their use in extreme environments such as polar regions and outer space. The presented systematic study addresses this challenge by modulating and tailoring the electrolyte composition for SIBs, enabling ultra-low temperature operation down to -110 degrees C for the first time. The comprehensive molecular dynamic and density functional theory calculations combined with experimental Raman spectroscopy and nuclear magnetic resonance studies of advanced electrolytes provided a deeper mechanistic understanding of the solvation structures and their impact on electrochemical performance. By varying the solvent composition with a combination of tetrahydrofuran and 2-Methyltetrahydrofuran solvents and sodium hexafluorophosphate (NaPF6) salt, the freezing point, solubility, and Na+ solvation structure of the electrolyte is modulated and studied in detail. The extensive anion engagement in the optimized mix solvent electrolyte facilitated the formation of a stable and inorganic-rich solid electrolyte interphase layer, ensuring low overpotentials and uniform Na+ deposition, yielding superior cycling stability. As a result, the developed electrolyte enables SIBs to achieve reversible capacities of 88 mAh g(-1) at -60 degrees C and 50 mAh g(-1) at -100 degrees C. These insights may contribute to developing improved energy storage devices suitable for challenging environmental conditions.
Keywords: contact-ion pair; solid electrolyte interphase (SEI); solvation; ultra-low temperature; XPS-depth Profiling